2020
DOI: 10.3389/fpubh.2019.00394
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, and Control of Arterial Hypertension in a Russian Population. The Ural Eye and Medical Study

Abstract: Background: Applying the criteria recently published by the American College of Cardiology/American Heart Association for the definition of arterial hypertension, we investigated prevalence and awareness of arterial hypertension in Russia. This new definition differentiates between normal BP [SBP (systolic blood pressure)/DBP (diastolic blood pressure) < 120/80 mmHg], elevated BP (SBP 120-129 mmHg; DBP < 80 mmHg), hypertension stage 1 (SBP 130-139 mmHg or DBP 80-89 mmHg), hypertension stage 2 (SBP ≥ 140 and ≤1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…Consistently, previous studies suggested that having older age and obesity were associated with a higher prevalence of hypertension [ 7 – 9 , 21 ], diabetes [ 16 , 22 , 26 ] and hypercholesterolemia [ 17 ]. We also found that being low-educated was associated with a higher prevalence of hypertension, and lower rates of awareness, treatment and control of hypertension and hypercholesterolemia than those being high-educated, which were consistent with previous findings [ 8 , 9 , 23 ]. However, in our study, individuals with disadvantaged socioeconomic position (being low-educated or having a low level of household amenities) were less likely to have hypercholesterolemia than those with advantaged socioeconomic position.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently, previous studies suggested that having older age and obesity were associated with a higher prevalence of hypertension [ 7 – 9 , 21 ], diabetes [ 16 , 22 , 26 ] and hypercholesterolemia [ 17 ]. We also found that being low-educated was associated with a higher prevalence of hypertension, and lower rates of awareness, treatment and control of hypertension and hypercholesterolemia than those being high-educated, which were consistent with previous findings [ 8 , 9 , 23 ]. However, in our study, individuals with disadvantaged socioeconomic position (being low-educated or having a low level of household amenities) were less likely to have hypercholesterolemia than those with advantaged socioeconomic position.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we also found that alcohol consumers had a significantly higher prevalence of hypertension and hypercholesterolemia, but lower rates of awareness, treatment and control of hypertension, hypercholesterolemia and diabetes, than non-alcohol consumers. One study in Russia and another study in Argentina, Chile and Uruguay also indicated positive associations between alcohol consumption and the prevalence of hypertension [ 8 , 37 ]. Alcohol consumption is an important risk factor for cardiovascular disease and total mortality in CEE countries.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the various stages of HTN do not show a clear upward trend but rather oscillate year by year represents a complex phenomenon reflecting multiple underlying influences, including population changes, public health interventions, and variations in treatment adherence. This fluctuation in HTN prevalence rates has been observed in several studies over time and can be attributed to social, economic, and health factors (1115) .…”
Section: Discussionmentioning
confidence: 79%
“…This figure is considerably lower compared to other international studies, where the prevalence tends to be higher. For instance, a recent systematic review that included eight observational studies in emergency departments reported a global prevalence of hypertensive crisis at 1.2% (16) , while the work of Bikbov et al (11) reported a prevalence of 2.7%.…”
Section: Prevalence and Trends Of Different Stages Of Hypertensionmentioning
confidence: 99%
“…Additionally, the consensus in many countries is that the new definition of stage 1 hypertension can enhance awareness on the risk of CVD, thereby improving vascular health, but individuals in lowincome countries face more challenges than those in highincome countries when it comes to public health (24)(25)(26). The prevalence of stage 1 hypertension in developing countries is high but often underestimated due to its asymptomatic nature, thereby it seriously endangers human life and brings heavy economic burden to the society (27). According to previous research, the prevention and treatment of stage 1 hypertension in the rural areas of China should be improved because the current level of cognition, treatment, and control is low (28,29).…”
Section: Discussionmentioning
confidence: 99%